Management of Papillary Carcinoma of Thyroid with Pulmonary Metastases in Institute of Nuclear Medicine and Allied Sciences, Rajshahi – Two Case Reports - Shah, Md Kabiruzzaman; Begum, Nasrin; Hossain, Mosharof; Ahmed, Parvez; Chawdhuary, Sariful Islam; Ahsan, M Shamim (Bangladesh Journal of Nuclear Medicine, 2018)
Papillary thyroid carcinoma with pulmonary metastasis is relatively uncommon which can be treated with radioactive iodine therapy. Here, our experiences with two cases of papillary thyroid carcinoma with pulmonary metastases in young patients are discussed. Bangladesh J. Nuclear Med. 18(2): 179-182, July 2015